Pengaruh Body Image Terhadap Kepercayaan Diri Remaja Kelas VIII SMP N 30 Semarang Yang Mengunggah Foto Selfie Di Media Sosial Instagram - Rachel Veronik; Eka Sari Setianingsih; Desi Maulia (Departement of Mathematics Education, 2024)
The study aims to find out the influence of body image on the self-confidence of high school 8th grade students N 30 Semarang who uploaded selfie photos on social media instagram. By means of the quantitative method with 97 female students respondents, the results of the normality test analysis in this study obtained a significant value of 0.200 and then on the linearity test obtains a value of 0,316. The simple linear regression test found the result of the regression coefficient value of the body image variable at 0.310 showing that if the variable body image has an increase then it can lower the self confidence variabel of teenagers who upload a selfie photo on social network instagram by 31% with a determination coeffice value of 0.0107 or 10.7% negative, meaning that if higher the level of body image confidence then adolescents expect selfie pictures on social networks will decrease. So it can be said that